PENGARUH VARIASI PERSENTASE EKSTRAK JANGKRIK (Gryllus sp Walk) YANG BERBEDA TERHADAP TINGKAT SURVIVAL RATE BENIH IKAN MAS KOKI (Carrasius auratus L) - Elrifadah Elrifadah; Yulius Kisworo (EnviroScienteae, 2013)
This study Aims to Determine the effect of different variations on survival seed cicada goldfish. The method used in this study is completely randomized design with 3 treatments (A = 3%, B = 5%, and C = 7%) and three replications. From these results Obtained survival rate to 83.0% Obtained treatment A, B Obtained 88.33% and 80.0% Obtained C treatment. Then the results of analysis of variance accept the hypothesis Ho that the percentage variation of different cicada extract (3%, 5% and 7%) did not Affect the survival rate of seedlings goldfish. During the last condition of water quality research support for seed viability parameters goldfish.